Brand Equity of Team Sport Towards Sponsorship in Indonesian Football Club - Syauqy Lukman, Reza Ashari Nasution (ITB, 2010)
This is a study concerning the result of sports sponsorship where the research focuses on how would a specific construct ofBrand Equity Would corrlate with the sponsorship outcome. The study takes one of the forerunners of professional football (soccer) club as the object. Persib (Persatuan SepakBola Indonesia Bandung), a football club which resides in Bandung. Persib has proven to be one of the most prominent football club in terms of business, fans, and professionalism. Each home game are watched by a minimum number of 40.000 spectators, and the company itself, PT. PBB (Persib Bandung Bermartabat, Inc.) has managed to generate a yearly income of approx. 12 Billion Rupiahs, income which is considered as the largest from a professional footbal club in Indonesia.